2014
DOI: 10.4014/jmb.1304.04036
|View full text |Cite
|
Sign up to set email alerts
|

Gene Cloning and Characterization of an α-Amylase from Alteromonas macleodii B7 for Enteromorpha Polysaccharide Degradation

Abstract: Enteromorpha polysaccharides (EP) extracted from green algae have displayed a wide variety of biological activities. However, their high molecular weight leads to a high viscosity and low solubility, and therefore, greatly restrains their application. To solve this problem, bacteria from the surface of Enteromorpha were screened, and an Alteromonas macleodii strain B7 was found to be able to decrease the molecular weight of EP in culture media. Proteins harvested from the supernatant of the A. macleodii B7 cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Among the identified species, the most common biotechnological function was associated with bioremediation, while subsequent common capabilities were plant growth promotion, plant systemic resistance, and biological syntheses of biocompatible nanometal and biodegradable polymers. We would like to note several interesting species that harbour unique abilities or products, namely lead, cadmium and zinc biosorption mechanism in A. macleodii ( Loaëc et al 1997 ); halotolerant and psychrotolerant α-amylase with broad pH tolerance in A. macleodii ( Han et al 2014 ); skeletal muscle relaxation properties and central nervous system (CNS) depressants in B. cereus ( Kumar et al 2014 ); antileukaemic and antineoplastic L-asparaginase in B. aryabhattai ( Singh & Srivastava 2014 ); polyhydroxyalkanoate (PHA) synthesis in P. putida ( Wang & Nomura 2010 ); biodegradation of highly explosive pentaerythritol tetranitrate (PETN) by E. cloacae ( Binks et al 1996 ); as well as antibacterial, immunosuppressive and anticancer prodigiosin in P. denitrificans ( Sertan-de Guzman et al 2007 ).…”
mentioning
confidence: 99%
“…Among the identified species, the most common biotechnological function was associated with bioremediation, while subsequent common capabilities were plant growth promotion, plant systemic resistance, and biological syntheses of biocompatible nanometal and biodegradable polymers. We would like to note several interesting species that harbour unique abilities or products, namely lead, cadmium and zinc biosorption mechanism in A. macleodii ( Loaëc et al 1997 ); halotolerant and psychrotolerant α-amylase with broad pH tolerance in A. macleodii ( Han et al 2014 ); skeletal muscle relaxation properties and central nervous system (CNS) depressants in B. cereus ( Kumar et al 2014 ); antileukaemic and antineoplastic L-asparaginase in B. aryabhattai ( Singh & Srivastava 2014 ); polyhydroxyalkanoate (PHA) synthesis in P. putida ( Wang & Nomura 2010 ); biodegradation of highly explosive pentaerythritol tetranitrate (PETN) by E. cloacae ( Binks et al 1996 ); as well as antibacterial, immunosuppressive and anticancer prodigiosin in P. denitrificans ( Sertan-de Guzman et al 2007 ).…”
mentioning
confidence: 99%
“…A321 [Li et al, 2013] was recently reported. A. macleodii B7 from the surface of E. prolifera decreased the molecular weight of EP in culture media [Han et al, 2014]. Alteromonas sp.…”
Section: Discussionmentioning
confidence: 97%
“…The process of hydrolyzing EP requires a different set of enzymes. In this regard, the microbial hydrolysis of EP by Alteromonas macleodii B7 [Han et al, 2014] and Alteromonas sp. A321 [Li et al, 2013] was recently reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations